Media Analysis of Donald Trump's Policies Toward the Islamic World - Yusuf, Rusydi Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
There is no denying the power of the mass media, including radio, television, and newspapers. They have the ability to shape the news that is reported so that people who hear it will believe it to be true, even when that may not always be the case. Similar to what happened with the news that was reported on Donald Trump's policy regarding the ban on seven Muslim citizens entering the country, part of the news that was reported was also the product of media fabrication, meaning that while some of the information appeared to be true, it was actually created by the media. Based on an examination of Donald Trump's immigration policies, which were created to safeguard national interests against terrorism. The approaches of positivism and constructivism are discussed in this discussion of how the media presents news. According to positivism, news is presented without editing and as it is, while according to constructivism, news is first constructed to make its content seem more dramatic and true.